The Effectiveness of Simulation-Based Micro Teaching Model in Improving Students' Teaching Skills as Prospective Teachers - Euis Latipah; Lisda Aulia Apriani; Silvi Sofiatul Alawiyah; Tri Fatmah Nurhalizah (Penerbit Hellow Pustaka, 2026)
This study investigates the effectiveness of simulation-based microteaching models in optimizing the teaching skills of students preparing to become teachers. Education is recognized as a conscious and planned effort to develop the overall potential of students, including spiritual strength, self-control, personality, intelligence, noble character, and skills that are relevant to individuals and society. In this context, the role of teachers is fundamental because they not only influence the sustainability of the education system but are also crucial in forming positive characters and triggering students' creativity. Therefore, simulation-based microteaching is present as an innovative approach that allows students to practice teaching in a controlled environment and get direct feedback for improvement. Through the literature review method, this study analyzes the concept of microteaching, the role of simulation as an effective learning strategy, and essential teaching skills for prospective teachers. The results of the literature review indicate that simulation-based microteaching is very effective in mastering teaching techniques and forming the mental, spiritual, and social readiness of prospective teachers. This method also develops the ability to guide discussions, ask critical questions, explain material in a structured manner, and vary in learning. Therefore, simulation-based microteaching is a vital strategy to prepare prospective teachers who are professional, competent, and adaptive. Through the literature review method, this study analyzes the concept of microteaching, the role of simulation as an effective learning strategy, and essential teaching skills for prospective teachers. The results of the literature review indicate that simulation-based microteaching is very effective in mastering teaching techniques and forming the mental, spiritual, and social readiness of prospective teachers. This method also develops the ability to guide discussions, ask critical questions, explain material in a structured manner, and vary in learning. Therefore, simulation-based microteaching is a vital strategy to prepare prospective teachers who are professional, competent, and adaptive.